To what extent can the chosen blood pressure measurement technique affect the outcomes of an observational survey? - Mayer, Otto; Seidlerová, Jitka; Mateřánková, Markéta; Gelžinský, Julius; Mareš, Štěpán; Rychecká, Martina; Svobodová, Veronika; Bruthans, Jan; Filipovský, Jan (Journal of comparative effectiveness research, 2019)
Aim: We analyzed to what extent measurement protocol influenced individual blood pressure (BP) and achievement of treatment target in patients with coronary heart disease. Methods: In a subsample of Czech EUROASPIRE III-V survey participants (n = 913), we compared the per-protocol BP measurement (by automated oscillometric device OMRON at the beginning of survey procedure) with control auscultatory measurement (by physician during interview). Results: Per-protocol approach produced significantly (p < 0.0001) higher BP values (by 9/6 mmHg in median) than auscultatory measurements and led to markedly higher proportion of patients over target BP (less than 140/90 mmHg; 59.3 vs 34.9% [p < 0.0001], per-protocol vs auscultatory technique, respectively). Conclusion: Per-protocol oscillometric technique was not equivalent to conventional auscultatory measurement and seriously over-rated the real nonachievement of BP target in observational surveys.
Keywords: Oscillometry; Female; oscilometrie; ženské pohlaví; průřezové studie; lidé; treatment target adherence; unattended automated oscillometric; krevní tlak; auscultatory; Cross-Sectional Studies; Male; Aged; automated oscillometric; Blood Pressure Determination; měření krevního tlaku; lidé středního věku; senioři; mužské pohlaví; EUROASPIRE; Blood Pressure; Middle Aged; Clinical Protocols; coronary heart disease; klinické protokoly; Humans